Climat, Wether and Crops in India - D.Lenka; D.Lenka (Ludhiana Kalyani, 1998)
This book is designed to give a comprehensive idea to the undergraduate and post graguate students of Agriculture University on climat, weather and crops.
Wind Moister Temperature Evapotranspiration
Keywords: Wind ,Moister, Temperature